Feeding the five thousand: studies in the Judaic background of Mark 6:30-44 par. and John 6:1-15 - Aus, Roger David (Studies in Judaism, 2010)
Famine, the 'Omer, and barley bread -- Similarities between Elisha and Jesus, especially as miraacle-workers -- Jesus as a teacher with disciples, and Elisha as a teacher with disciples -- Denarii -- Baal-shalishah, Shalishah, and John 6 -- Jesus' praying, and Elisha's praying -- Doubling, garden beds and rows, according to hundreds and fifties, and groups -- Eating to satiety, and saying grace after meals -- Baskets full of left over pieces -- 5000 men -- Bethsaida as a possible site of the feeding, and the Livia/Julia cult -- Markan redaction in 6:30-44, and Johannine redaction in 6:1-15 -- The Markan and the Johannine contexts -- The Semitic background of the feeding of the 5000, and possible Hellenistic parallels -- Major motifs in the narrative -- The genre -- The historicity -- Two Markan feeding narratives, and the feeding of the 5000 as part of a miracle collection